SAPHIR: real-world clinical research platform for molecular testing, treatment, and clinical and patient-reported outcomes in patients with gastroesophageal cancer in Germany - K. Potthoff; T. Dechow; S. Lorenzen; A. Reinacher-Schick; A. Binninger; C. Matillon; H.-U. Siebenbach; I. Haffner; U. Hacker; H. Bläker; F. Lordick (ESMO Real World Data and Digital Oncology)
Background: The treatment landscape of gastroesophageal cancer (GEC) is evolving. A better understanding of GEC biology and novel effective drugs would enhance the standard of care. To further improve outcomes for patients with GEC, it is crucial to evaluate treatment, response, survival, and patient-reported quality of life (QoL) in a real-world setting. Materials and methods: SAPHIR is a prospective and retrospective, observational, multicenter, national cohort study on esophageal, gastric, or gastroesophageal junction cancers. The study is aimed at enrolling 900 patients with stage IV GEC receiving first-line systemic therapy (prospective data collection). Patients are enrolled at ∼150 sites from different health care sectors in Germany. Recruitment started in quarter 4 (Q4)/2019. Each patient will be observed for a maximum of 2 years. In a satellite project, recruitment of another 200 patients with stage IB-III GEC receiving pre-/perioperative chemotherapy or radiochemotherapy was conducted in Q1-2/2022 (retrospective, one-time data collection). SAPHIR will provide real-world data (RWD) on treatment preferences, molecular testing, and clinical outcomes including overall and health-related QoL. Furthermore, patients can give consent for donation of tumor tissue obtained during the course of routine clinical care for centralized biomarker research. Descriptive statistics and explorative analyses will be carried out. Conclusions: SAPHIR aims to improve health care for patients with GEC by collecting RWD representative for all sectors in health care. This will provide information on routine clinical practice, efficacy, and evolving biomarker in GEC. Furthermore, evaluation of molecular data may allow for identification of response or resistance mechanisms to targeted and immunotherapy in GEC.